2002
DOI: 10.1091/mboc.13.6.mk0602002001
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of Dioxin Receptor to Active Transcription Sites

Abstract: The aryl hydrocarbon receptor (AhR or dioxin receptor) is a ligand-activated transcription factor that heterodimerizes with the AhR nuclear translocator (ARNT/HIF-1beta) to form an AhR/ARNT transcription factor complex. This complex binds to specific DNA sites in the regulatory domains of numerous target genes and mediates the biological effects of exogenous ligands. Herein, we have investigated the subcellular distribution of the AhR/ARNT complex in response to ligand stimulation, by using live-cell confocal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 50 publications
5
40
0
Order By: Relevance
“…4) (Tyagi et al, 2000;Tomura et al, 2001). For the aryl hydrocarbon receptor it was shown that foci correlated with transcription sites (Elbi et al, 2002) whereas for the GR, no clear correlation of foci with pre-mRNA synthesis sites could be demonstrated (van Steensel et al, 1995). Our results (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4) (Tyagi et al, 2000;Tomura et al, 2001). For the aryl hydrocarbon receptor it was shown that foci correlated with transcription sites (Elbi et al, 2002) whereas for the GR, no clear correlation of foci with pre-mRNA synthesis sites could be demonstrated (van Steensel et al, 1995). Our results (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The functional importance of subnuclear localization of transcription factors to discrete foci in chromatin has been widely reported (18,26,28,29), although studies on subnuclear diffusion dynamics have largely focused on the family of ligand-dependent nuclear hormone receptors. For example, the glucocorticoid receptor (27,35,36), thyroid hormone receptor (37), dioxin receptor (38), and proliferation-activated receptor (39) reportedly undergo liganddependent intranuclear redistribution into discrete foci representing transcriptional complexes. The pools of nuclear receptor in these foci undergo rapid (within seconds) exchange with a more highly mobile fraction in the nucleoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…We compared the nucleoplasmic distribution of p53 to that of the PP2Ac by high-resolution dual-staining indirect immunofluorescence microscopy (Van Steensel et al, 1996;Elbi et al, 2002). We observed significant colocalizations (yellow-orange) between p53 (red) and PP2Ac (green) 2 and 4 h after g-irradiation (panels g and j).…”
Section: P53 Associates With Pp2ac In Mcf-7 Cellsmentioning
confidence: 95%
“…Indirect immunofluorescence was performed as previously described (Elbi et al, 2002). Briefly, after exposure to 8 Gy -irradiation, cells were fixed with 2% paraformaldehyde in PBS.…”
Section: Expression and Purification Of Gst-p53 Proteinsmentioning
confidence: 99%